Outstanding library service to children : putting the core competencies to work - Cerny, Rosanne (Association for Library Service to Children, American Library Association, 2006)
What does it truly take to provide excellent library service to children? The Association for Library Service to Children (ALSC) has outlined seven core competencies—skills and best practices that are the building blocks for professional development for children's librarians. In this practical guide, three children's services experts bring these best practices to life. Each chapter, focusing on one of the competencies, gets new and experienced librarians up to speed fast by offering explanations, examples, and a substantial bibliography for more in-depth learning. Library managers gain trainin.